Unseen victims: why refugee women victims of gender-based violence do not receive assistance in the EU - Lilja, Inka (Publication series, 2020)
The HEUNI report "Unseen Victims" presents the manifestations and consequences of gender-based violence and the challenges in assisting victims of violence in the migration context. With this report we aim to increase the understanding of policymakers on the structural challenges asylum-seeking and refugee women who have experienced gender-based violence face.